EFFECT OF EFFECTIVE MICROORGANISMS ADDITION ON METHANE PRODUCTION FROM COFFEE HUSKS - Hasrul Anwar; Andhika Sukma; Ridho Ulya (Universitas Lambung Mangkurat, 2022)
Coffee husk is a lignocellulosic material which is abundant and can be used to produce biogas. This study compares the production of biogas produced from coffee husk substrate using cow dung and a mixture of cow dung and effective microorganisms. This experiment was carried out for 30 days in an anaerobic batch reactor with a reactor working volume of 3.6 L at mesophilic temperature. The parameters tested in this study were the lignocellulosic content of coffee husks, total solids (TS), volatile solids (VS), volatile fatty acids (VFA), chemical oxygen demand (COD), and the content of biogas produced from both variables. The lignocellulosic compositions obtained from this study were cellulose 65.90%, hemicellulose 24.95%, lignin 0.21%, pectin 0.42%, protein 0.81%, tannins 1.05%, caffeine 0.09%, and polyphenols. The values of Total Solids and Volatile Solids for the two variables are K-KS of 16.78% and 33.98% and K-KSEM of 24.87% and 48.42%, respectively. The total VFA for the two variables is 2.06% (v/v) for K-KS and 2.36% (v/v) for K-KSEM. The COD values for the K-KS and K-KSEM variables were 78.05% and 81.42%, respectively. The composition of biogas for K-KS is CH4 12.35%, CO2 21.68%, and H2 0.32%, while for K-KSEM it is CH4 19.64%, CO2 2.82%, and H2 0.35 %. The methane yields for the two variables, K-KS and K-KSEM, were 0.76 Nm3/kgCODremoval and 1.43 Nm3/kgCODremoval, respectively.Key words: anaerobic digestion, cow dung, rumen fluid, effective microorganism (EM), methane